A Practical Tool to Create Economic Opportunity for Low-Income Communities - Burke, Laura (International Finance Corporation, Washington, DC, 2018)
Private businesses and investors can create markets and accelerate growth for low-incomecommunities in emerging markets. In doing so, they benefit from estimates of poverty in thetargeted market segments they seek to serve. While national household surveys provide povertydata, they are often too costly and overly broad for the purposes of private enterprises. Use ofthe Poverty Probability Index can help businesses improve their estimates of poverty and therebybetter tailor their operations and strategies to specific populations.